Mikroskop Digital Berbasis Kamera Smartphone - Ariska, Melly; Alawiyah, Sakinah (Universitas Nurul Huda, 2019)
Technology in the world is growing, technological developments have an impact on the world of education. One of the uses of technology is with cellphones, where cellphones are included in technology that is very popular with everyone. Therefore, the microscope media is designed with a smartphone camera. It is expected that microscope learning media based on smartphone cameras is one of the alternative learning media in schools that do not have a light microscope. The smartphone camera-based digital microscope is classified as a laboratory tool (tool of practice) in learning physics, biology. This smartphone camera-based microscope produces a fairly good and clear image, this camera-based digital microscope is easily poisoned with material that is easily found in everyday life. The workings of a digital microscope based on a smartphone camera are almost the same as the way a light microscope works, only here use the help of a smartphone so that the image obtained is more clearly visible on the smartphone screen.